2016
DOI: 10.1016/j.tranon.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Losartan-Induced Increase in Functional Microvasculature and Drug Delivery in Pancreatic Ductal Adenocarcinoma

Abstract: PURPOSE: Losartan, an angiotensin II receptor blocker, can reduce desmoplasia and enhance drug delivery and efficacy through improving interstitial transport and vascular perfusion in pancreatic ductal adenocarcinoma (PDAC) models in mice. The purpose of this study was to determine whether magnetic resonance imaging (MRI) of magnetic iron oxide nanoparticles (MNPs) and micro–positron emission tomography (PET) measurements could respectively detect improvements in tumor vascular parameters and drug uptake in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…This receptor is a leading target in active clinical investigations for patients with PDAC (NCT01821729 and NCT03563248). An inhibitor of this receptor, Losartan, was shown to reduce intratumoral solid stress, leading to increased vascular perfusion and improved drug delivery (48,78). A major source of solid stress in PDAC tumors is hyaluronan (7), and the enzymes responsible for hyaluronan production are uniquely and specifically expressed in iCAFs (HAS1 and HAS2 in the human data; Has1 and Has2 in the mouse data).…”
Section: Discussionmentioning
confidence: 99%
“…This receptor is a leading target in active clinical investigations for patients with PDAC (NCT01821729 and NCT03563248). An inhibitor of this receptor, Losartan, was shown to reduce intratumoral solid stress, leading to increased vascular perfusion and improved drug delivery (48,78). A major source of solid stress in PDAC tumors is hyaluronan (7), and the enzymes responsible for hyaluronan production are uniquely and specifically expressed in iCAFs (HAS1 and HAS2 in the human data; Has1 and Has2 in the mouse data).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to tissue composition, the introduction of contrast agents, including magnetic iron nanoparticles such as ferumoxytol, reduces the T 1 , T 2 , and T 2 * of surrounding blood and tissue . Previous studies have demonstrated that comparing T 2 and T 2 * relaxation time constants before and after ferumoxytol can produce quantitative biomarkers of vessel density and size, with T 2 * being critical for calculation of these parameters. However, in organs that are subject to motion and require breath hold imaging for precise relaxometry, it is difficult to gather simultaneous acquisition of all relaxation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, collagenase cannot be used systemically, which limits its application. One of many systemic agents under investigation includes the antihypertensive agent losartan, which reportedly decreased collagen deposition, increased blood flow as well as uptake of the cytotoxic agent in pancreatic cancer [ 40 ].…”
Section: Modes Of Ov Deliverymentioning
confidence: 99%